(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Demodicosis is one of the most common dermatoses. Demodex blepharitis accounts for 39% to 88% of all cases of inflammatory eyelid disorders. Purpose: To assess the prevalence of meibomian gland dysfunction (MGD) accompanied by palpebral demodicosis in patients with type 2 diabetes mellitus (T2DM). Material and Methods: Seventy-five patients (150 eyes; mean age, 54 ± 8 years; 34 men (45.3%) and 41 women (54.7%)) with compensated T2DM and symptoms of MGD were included in this study. Patients underwent visual acuity assessment, biomicroscopy, ophthalmoscopy, compression test (to assess meibomian gland secretions), meibography, Schirmer test, tear film breakup time, and laboratory test for Demodex mites, and laboratory studies (lipidogram, fasting blood sugar, and glycated hemoglobin). In addition, they were administered the Ocular Surface Disease Index (OSDI) questionnaire. Moreover, diabetes duration, blood sugar levels, and type of therapy for diabetes were assessed. Results: Palpebral demodicosis was twice as common in patients with T2DM duration more than 10 years as in those with T2DM duration less than 10 years (p = 0.002). Our meibography study found changes in meibomian glands in 90% of diabetics with palpebral demodicosis, with the mean meibograde score of 5.0 ± 0.9 points, which indicated a predominance of moderate MGD. Conclusion: Metabolic defects in patients with T2DM contribute to the development of palpebral demodicosis that was found in 61.3% of patients. Mixed type dry eye disease was found in T2DM patients with palpebral demodicosis, which required treatment for MGD and restoration of the tear film aqueous layer.